Glycosomal bromodomain factor 1 from Trypanosoma cruzi enhances trypomastigote cell infection and intracellular amastigote growth - Ritagliati, Carla (2015)
Acetylation is a ubiquitous protein modification present in prokaryotic and eukaryotic cells that participates in the regulation of many cellular processes. The bromodomain is the only domain known to bind acetylated lysine residues. In the last few years, many bromodomain inhibitors have been developed in order to treat diseases caused by aberrant acetylation of lysine residues and have been tested as anti-parasitic drugs. In the present paper, we report the first characterization of Trypanosoma cruzi bromodomain factor 1 (TcBDF1). TcBDF1 is expressed in all life cycle stages, but it is developmentally regulated. It localizes in the glycosomes directed by a PTS2 (peroxisome-targeting signal 2) sequence. The overexpression of wild-type TcBDF1 is detrimental for epimastigotes, but it enhances the infectivity rate of trypomastigotes and the replication of amastigotes. On the other hand, the overexpression of a mutated version of TcBDF1 has no effect on epimastigotes, but it does negatively affect trypomastigotes' infection and amastigotes' replication.